Anthropogenic nutrient loading affects both individual species and the trophic structure of river fish communities - Horka, Petra; Musilova, Zuzana; Holubova, Katerina; Jandova, Katerina; Kukla, Jaroslav; Rutkayova, Jitka; Jones, John Iwan (Frontiers in Ecology and Evolution, 2023)
Although the concept of trophic interactions has been used for long time, there are still considerable gaps in our understanding of the effect of various environmental factors on trophic interactions of river fish assemblages. Carbon (δ13C) and nitrogen (δ15N) stable isotope ratios of 20 species of fish belonging to both eurytopic and rheophilic ecological groups from a large temperate rivers were used to evaluate overall trophic niche use and trophic position of species, and to find out how environmental variability associated with nutrient loading affects individual and community-wide aspects of trophic structure. The study was carried out at eleven sites along the European rivers Vltava and Elbe, representing a continuous gradient of pollution and habitat degradation. Corrected Standard Ellipse Area (SEAc) was significantly larger for the group of eurytopic ecological species than for rheophilic species. Despite narrower isotopic niche space, rheophilic fish species occupied a higher trophic position, suggesting that these species use resources more enriched in 15N. Of the 11 environmental variables tested, nutrients had a significant effect on trophic niche area of species (SEAc), indicating that eutrophication is of critical importance for fish assemblages. Isotopic niche area of species was found to be positively influenced by total phosphorus, and negatively affected by concentrations of nitrate (N-NO3-) and ammonia (N-NH4+). A negative association between oxygen demand and a measure of trophic diversity - mean distance to centroid (CD) and a measure of density and clustering of species - mean nearest neighbour distance (MNND) were found, indicating that the oxygen demand is a key factor influencing community trophic structure. An observed pattern where nutrient loading influenced both individual species and trophic structure of the fish assemblage provides strong support for an anthropogenic influence on riverine food webs.